Nematode larvae infecting Priacanthus arenatus Cuvier, 1829 (Pisces: Teleostei) in Brazil - KURAIEM,BIANCA P. (2016)
From July to December, 2013, thirty Priacanthus arenatus specimens commercialized in the cities of Niterói and Rio de Janeiro, State of Rio de Janeiro, were acquired. The fish were necropsied and filleted to investigate the presence of nematode larvae. Twenty fish (66.7%) out of the total were parasitized by nematode larvae. A total of 2024 larvae were collected; among them, 30 third-instar larvae of Anisakis sp. showed prevalence (P) = 20%, mean abundance (MA) = 1, and the mean intensity (MI) = 5, and infection sites (IS) = caecum, stomach, liver, and mesentery; and 1,994 third-instar larvae (1,757 encysted and 237 free) of Hysterothylacium deardorffoverstreetorum with P = 66.7%, MA = 66.5, and MI = 99.7, and IS = spleen, caecum, stomach, liver, mesentery, and abdominal muscle. This is the first study to report H. deardorffoverstreetorum and Anisakis sp. larvae parasitizing P. arenatus.